Pelatihan Budidaya Maggot BSF sebagai Upaya Pemanfaatan Limbah Organik Rumah Tangga untuk Alternatif Pakan Ternak - Satyarso, Muhammad Ardian Candra; Muhajir, Muhammad; Yotenka, Rahmadi (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Household organic waste management remains a challenge in Bulu Village, in Bulu and Ngentak Hamlets. Improperly managed waste can generate unpleasant odors, attract disease vectors, and pollute the environment, although it can be utilized as a medium for cultivating Black Soldier Fly (BSF) larvae. This community service program aimed to improve community understanding and provide participants with initial practical experience in utilizing household organic waste through BSF larvae cultivation, which has the potential to support the provision of alternative animal feed. The program involved 23 participants and was conducted through a survey and interviews, educational sessions, demonstrations, hands-on cultivation practice, discussions, and an assessment of participants’ understanding. The assessment used five pretest and posttest questions covering the benefits of BSF larvae, required tools and materials, cultivation procedures, harvesting time, and their utilization as animal feed. The results showed that the average percentage of correct answers increased from 5.2% before the training to 100% after the training. The greatest improvement occurred in understanding the cultivation procedures, which increased from 0% to 100%. The program also produced a pilot cultivation medium using 5 kg of household organic waste, which was handed over to community representatives for maintenance and monitoring. These results indicate that combining educational sessions, demonstrations, and hands-on practice was effective in improving participants’ short-term understanding and providing initial practical experience. Thus, the program introduced BSF larvae cultivation as a productive alternative for organic waste management with the potential to support the provision of animal feed derived from local resources.